DEVELOPMENT TEST SYSTEM BASED ON LINEAR EQUATIONS TWO VARIABLE REVISED TAXONOMY BLOOM TO MEASURE HIGH ORDER THINKING SKILLS AT STUDENT CLASS VIII SMPN SUNGGUMINASA GOWA - Sri Wahyuni (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2017)
High-level thinking skills based on a revised Bloom's taxonomy is an ability that involves the analysis, evaluation, and create the dikombainkan with dimensions of factual knowledge, conceptual and procedural. This research is the development (Research and Development), which aims to generate test Systems of Linear Equations Two Variables based on a revised taxonomy Bloom qualified to measure high-level thinking skills class VIII SMPN Sungguminasa Gowa. The subjects were the students of class VIII SMPN 4 Sungguminasa Gowa 117 people composed of 80 women and 37 men. Procedure development of instruments that are used to adopt the design development of formative research by Tesmer comprising the step of preliminary, namely the determination of the place and the subject of research, the stage of self-evaluation that is, identifying the learning material of mathematics, knowing the number of students and the information that the students have not got and do the problems higher level thinking and preparation of design problems of high-level description of thinking and formative stages of evaluation (expert review, evaluation of one to one, small group evaluation, and field test). The results showed that the test instrument system of linear equations of two variables based on Bloom's taxonomy developed revisions of quality in this case are valid, reliable, and has the potential effect of high-level thinking skills test that can be completed by students according to the level of mathematical ability. High-ability students can take the test high capability to the level of creation, capable students were able to take the test high caliber to the level evaluate, and low-ability students are only able to work on high-ability test at level analyzes